20 years of national wildlife disease surveillance. (27th April 2019) - Holmes, J Paul; Duff, J Paul; Barlow, Alex; Everest, Dave; Man, Cat; Smith, Freya; Twomey, Fin
Abstract : The need for wildlife surveillance is as great now as it ever has been. Here, members of the APHA's Diseases of Wildlife Scheme explain why their work is important.